Influence of Eucalyptus spp. essential oils and tannins on herbivory (Research, Society and Development, 2022)
Eucalyptus (family Myrtaceae), a native plant from Australia, is a genus cultivated due to its oil, gum, pulp and timber used worldwide for different commercial applications. It is a plant with significant economic importance and possibly its cultivation, in Brazil and other countries, has reduced the exploitation of native trees. The secondary metabolism of Eucalyptus, as usually found in plants, produces essential oils and tannins, which may interfere in the consumption of plants by wild animals. The goal of the present work was to investigate the influence of essential oil and tannins concentration on the herbivory of seven Eucalyptus taxa. Essential oils composition for all species investigated were characterized by CG MS HS-Trap analysis. The lowest hebivory rate were associated to Urocam, Grancam and Eucalyptus benthamii. Those taxa were associated with the presence of mix oil compounds, α/β-Pinene, Pinocarveol, α-Terpineol and Tannins. Tannins concentrations and essential oil are an important factor that contributes to the plant protection against herbivory.